Kepemilikan Asing, Kepemilikan Manajerial, Profitabilitas, Media Exposure dan Intensitas Pengungkapan Corporate Social Responsibility - Ratnadewi, Desi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p12, 2024)
CSR disclosure is the disclosure of all information on social activities carried out by the company. The research aims to determine the influence of foreign ownership, managerial ownership, profitability, and media exposure on the intensity of CSR disclosure. This research uses a sampling method, namely non-probability sampling with purposive sampling technique. There are 173 companies with 519 observations. The data analysis technique used is multiple linear regression analysis. The research results show that profitability and media exposure have a positive effect on the intensity of corporate social responsibility disclosure. Managerial ownership has a negative effect on the intensity of corporate social responsibility disclosure. Foreign ownership has no effect on the intensity of corporate social responsibility disclosure. Keywords: Foreign Ownership; Manajerial Ownership; Profitability; Media Exposure; Corporate Social Responsibility Disclosure